Status of infection prevention and control in Cameroon healthcare facilities: lessons learned from the WHO COVID-19 scorecard tool under the hierarchy of control model - Boris Arnaud Kouomogne Nteungue; Erick Tandi; Chanceline Bilounga Ndongo; Tania Bissouma-Ledjou; Alphonse Acho; Jeffrey Campbell; Dieudonnée Reine Ndougou; Reverien Habimana; Ambomo Sylvie Myriam; Bertolt Brecht Kouam Nteungue; Oyono Yannick; Louis Joss Bitang; et al. (Infection Prevention in Practice)
Summary: Background: Infection prevention and control (IPC) helps prevent disease transmission in healthcare facilities. There is a dearth of information on the implementation of IPC during the COVID-19 outbreak in Cameroon using the recommended WHO COVID-19 IPC scorecard tool. The present study assessed healthcare facilities' compliance to IPC by continuous assessments, with an evaluation of the tool using the hierarchy of control theory. Methods: This cross-sectional study was conducted in the 10 administrative regions of Cameroon by evaluating healthcare facilities prioritized by the Ministry of Public Health as high-risk facilities between March 2020 and November 2023. Comparisons were made regarding the facilities' ownership, level and status. Results: 2,188 assessments from 1,358 healthcare facilities were collected. The median IPC scores at each evaluation were between the intermediate and advanced level, with a bias linked with decreasing selection of facilities. However, only 172 (13%) healthcare facilities achieved advanced IPC score (≥75%). Higher IPC scores were found in hospitals (p<0.001) and in private facilities (p=0.02). Predictors of good IPC compliance were hospital (OR=3.7, CI: 1.4–9.8) and private facility (OR=2.3, CI: 1.6–3.3). The tool met the five domains of the hierarchy of control model. Conclusion: Repeated IPC assessments using recommended tools contribute to a better compliance of IPC by healthcare facilities in resources constrained settings.